Draft Annual Plan 2011 - 12 Volume -I (Narrative) Government of Rajasthan - Planning Commission (Planning Commission, 2011)
Rajasthan, in its present form, is a conglomeration of 19 princely States and 3 chiefships, which varies in size, population, administrative efficiency and the level of socio-economic development. Rajasthan is the largest State of India with 10.41 percent geographical area spread over 3.42 lakh square kms. It is administratively divided into 7 divisions, 33 districts, 192 sub-divisions, 244 tehsils and 249 development blocks.
Government of Rajasthan, Planning Department